2021
DOI: 10.1021/acs.accounts.0c00710
|View full text |Cite
|
Sign up to set email alerts
|

Metamorphoses of Cesium Lead Halide Nanocrystals

Abstract: Conspectus Following the impressive development of bulk lead-based perovskite photovoltaics, the “perovskite fever” did not spare nanochemistry. In just a few years, colloidal cesium lead halide perovskite nanocrystals have conquered researchers worldwide with their easy synthesis and color-pure photoluminescence. These nanomaterials promise cheap solution-processed lasers, scintillators, and light-emitting diodes of record brightness and efficiency. However, that promise is threatened by poor st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 58 publications
1
43
0
Order By: Relevance
“…Cesium lead halide perovskite (LHP) CsPbX 3 (X = Cl, Br, I, or their mixture) nanocrystals (NCs) have attracted extensive interests due to their fascinating optical and electronic properties, which can find promising applications in photovoltaics and optoelectronics. [1][2][3][4][5][6][7][8] However, CsPbX 3 LHPs are direct bandgap semiconductors with bandgaps ranging between ∼3.1-1.7 eV (∼410-700 nm), [9][10][11][12][13] yielding photoluminescence (PL) properties limited to the visible spectral domain. It has been shown that introducing intermediate states in the mid bandgap of the host by metal ions doping, particularly for Yb 3+ with emission at ∼1.0 μm, is an effective strategy to tune the emission of LHP hosts to the near-infrared (NIR) region.…”
Section: Introductionmentioning
confidence: 99%
“…Cesium lead halide perovskite (LHP) CsPbX 3 (X = Cl, Br, I, or their mixture) nanocrystals (NCs) have attracted extensive interests due to their fascinating optical and electronic properties, which can find promising applications in photovoltaics and optoelectronics. [1][2][3][4][5][6][7][8] However, CsPbX 3 LHPs are direct bandgap semiconductors with bandgaps ranging between ∼3.1-1.7 eV (∼410-700 nm), [9][10][11][12][13] yielding photoluminescence (PL) properties limited to the visible spectral domain. It has been shown that introducing intermediate states in the mid bandgap of the host by metal ions doping, particularly for Yb 3+ with emission at ∼1.0 μm, is an effective strategy to tune the emission of LHP hosts to the near-infrared (NIR) region.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in a humid environment both 1D CsMnBr Cesium lead halide perovskite CsPbX 3 (X: Cl, Br, I) nanocrystals (NCs) with narrow photoluminescence (PL) emission band have been shown to be good emitters of red, green and blue light. [1][2][3][4][5][6][7][8][9][10][11] Major issues about these lead halide perovskites are their toxicity and poor stability. [12] This has triggered the development of lead-free metal halide perovskite NCs.…”
mentioning
confidence: 99%
“…One example is the field of colloidal semiconductors, where lead-based NCs are among the most explored compounds due to the appealing optoelectronic properties demonstrated by lead halide perovskites in the UV-VIS and by lead chalcogenides in the IR spectral ranges. 6,7,12,13,19 There, the combination of as little as four elements (Cs, Pb, X and E, where X = F, Cl, Br or I and E = S, Se or Te) can yield NCs of a variety of phases: the binaries CsX, PbX2 and PbE, 6,7,[20][21][22] the well-known cesium lead halides (Cs4PbX6, CsPbX3, and CsPb2X5), 12,19,23,24 and the still little explored lead chalcohalides (Pb4S3Br2 and Pb4S3I2). 25,26 All these compounds are often obtained under similar reaction conditions, and can therefore compete during the synthesis, requiring a careful tuning of the synthetic protocols to achieve the impurity-free synthesis of the desired product.…”
Section: Introductionmentioning
confidence: 99%